Safety evaluation of Oral NSAID Treatment on Blood Pressure in Osteoarthritis Patients: Preventive study to Cardiovascular Events - Rosnarita, Intan Adevia; Khudzaifi, Muhammad; Priswa, Nindya (Majalah Farmaseutik, 2025)
Osteoarthritis (OA) is a degenerative joint disorder primarily affecting weight-bearing joints, causing pain, stiffness, and reduced mobility. Although there is no cure, symptom management focuses on pain relief and inflammation reduction, often through the use of nonsteroidal anti-inflammatory drugs (NSAIDs). However, NSAIDs are known to increase blood pressure, which poses concerns for long-term use, especially in patients with pre-existing cardiovascular risk factors. Given the chronic nature of OA and the common prescription of long-term NSAID therapy, it is important to assess their impact on blood pressure and cardiovascular health. This study aimed to evaluate the safety of oral NSAID therapy in terms of its effects on blood pressure in osteoarthritis patients at Dr. Moewardi Surakarta Regional General Hospital. An observational descriptive design was used with purposive sampling, analyzing data retrospectively from 35 OA patients receiving outpatient treatment for three months. The Wilcoxon signed-rank test was applied to assess changes in blood pressure, with statistical significance set at p<0.05. Results showed a significant increase in both systolic (11.3 ± 7.9 mmHg, p<0.05) and diastolic blood pressure (8.9 ± 7.0 mmHg, p<0.05) following NSAID use over the 3-month period. These findings highlight the need for careful monitoring of blood pressure in OA patients on long-term NSAID therapy, particularly those at higher cardiovascular risk. Long-term safety assessments are essential when considering NSAID treatment, and alternative therapeutic options should be considered for high-risk patients.